Types of linguistic means of influence in the election programs of candidates for the post of the President of Ukraine: on the material of the 2019 elections - Ситар, Ганна Василівна; Рогова, Марина Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The article analyzes the types of linguistic means of influence in the election programs of candidates for the post of President of Ukraine in 2019, used to establish or retain power and manipulate public consciousness and voter behavior. The following types of linguistic means of influence are distinguished: evaluative vocabulary, phraseological units, ideological clichés, metaphors, precedent phenomena, paraphrases, repetitions, gradation, rhetorical questions. It has been proven that evaluative vocabulary occupies a leading place among linguistic means of influence, creates a positive or negative assessment of an event or person. They attract attention and accurately express an emotionally expressive thought phraseological units, of which they have been modified. Ideological clichés are a means of stereotyping the voter’s thinking. The emotionality of the presentation is greatly enhanced by the political metaphor. In the election programs of 2019, the following types of metaphors are recorded: a metaphor of illness, a metaphor of collapse, a metaphor of a prison, a metaphor of space, a metaphor of welfare. Indirect names in the programs turned out to be solitary, descriptive names – periphrases, as well as precedent phenomena. Repetition is a useful means of persuading and instilling ideas in voters, used to highlight the main thesis of the program, the depiction of problems that threaten voters. The use of gradation helps the politician to highlight the complexity of the existing problem and convey to the electorate that only this politician can solve it. A rhetorical question is another means of activating voters’ attention, the main function of which is to induce voters to think and search for an answer to the question posed. Among the graphic means, the abnormal use of a capital letter to underline the most important lexeme (lexemes) and the use of quotation marks to change the nature of the assessment were recorded. A characteristic feature of the linguistic content of election programs is the layering of several different types of linguistic means, which has an expressive manipulative effect, creates the desired impression, evokes appropriate thoughts and encourages voting.